Insect assemblages associated with the exotic riparian shrub Russian olive (Elaeagnaceae), and co-occurring native shrubs in British Columbia, Canada. Issue 3 (7th December 2015) - Collette, Liana K.D.; Pither, Jason
Abstract: Russian olive ( Elaeagnus angustifolia Linnaeus; Elaeagnaceae) is an exotic shrub/tree that has become invasive in many riparian ecosystems throughout semi-arid, western North America, including southern British Columbia, Canada. Despite its prevalence and the potentially dramatic impacts it can have on riparian and aquatic ecosystems, little is known about the insect communities associated with Russian olive within its invaded range. At six sites throughout the Okanagan valley of southern British Columbia, Canada, we compared the diversity of insects associated with Russian olive plants to that of insects associated with two commonly co-occurring native plant species: Woods' rose ( Rosa woodsii Lindley; Rosaceae) and Saskatoon ( Amelanchier alnifolia (Nuttall) Nuttall ex Roemer; Rosaceae). Total abundance did not differ significantly among plant types. Family richness and Shannon diversity differed significantly between Woods' rose and Saskatoon, but not between either of these plant types and Russian olive. An abundance of Thripidae (Thysanoptera) on Russian olive and Tingidae (Hemiptera) on Saskatoon contributed to significant compositional differences among plant types. The families Chloropidae (Diptera), Heleomyzidae (Diptera), and Gryllidae (Orthoptera) were uniquely associated with Russian olive, albeit in low abundances. Our study provides valuable and novel information about the diversity of insects associated with an emerging plant invader of western Canada.